Integration Building Information Modeling and Lean Construction Technologies in the Iraqi Construction Sector: Benefits and Constraints (Journal of Engineering, 2023)
Building Information Modeling (BIM) and Lean Construction (LC) are two quickly growing applied research areas in construction management. This study focuses on identifying the most essential benefits and analyzing the most affecting constraints on the construction sector that construction players face as they attempt to combine BIM-LC in Iraqi construction. Experts assessed 30 benefits and 28 constraints from examining the previous literature, and a two-round Delphi survey formed the responses. Expert consensus analysis was utilized to elaborate and validate responses after descriptive statistical checks had been used for data processing.According to the study's findings, the benefits include ensuring the most effective project delivery method and shortening the design project life cycle. The building industry's procedures will incorporate suppliers. In contrast, the main constraints include the government rules and industry standards for BIM and LC are not obligatory, the absence of government funding and participation, and the industry's resistance to changing from customary operating methods. The study strategies and recommendations will enhance BIM-LC-LC implementation. It allows project partners to focus on addressing the challenges identified in this study and understand the benefits of BIM-LC to be an incentive to adopt them.